Experimental investigation of basalt rocks as storage material for high-temperature concentrated solar power plants. (August 2019) - Nahhas, Tamar; Py, Xavier; Sadiki, Najim
Abstract: Nowadays a sensible heat thermal energy storage system based on packed bed of rocks with air as a heat transfer fluid is considered a promising alternative and cost-effective solution for storage applications in concentrated solar power plants. Two varieties of basalt rocks collected from two different regions have been assessed for high-temperature packed-bed thermal energy storage. The most relevant thermo-physical and mechanical properties of the studied rocks as sensible heat storage materials were characterized. The influence of temperature on thermal expansion, density, specific heat capacity, thermal diffusivity, thermal conductivity and Young's modulus has been analyzed, as well as the crystalline phases and chemical compositions have been identified. Compared to molten salts and other available storage materials, the obtained results proved the potential of fine-grained basalt rocks to be used as filler material in energy storage applications suitable for high temperature concentrated solar power plants (up to 700 °C). In addition to their availability at low cost with low environmental impact, basalt rocks showed high thermo-physical properties and good thermal stability in this range of temperature. Highlights: Assessment of basalt as low-cost alternative sensible heat storage material. Basalt rocks from different regions were investigated for high-temperature air-rock packed bed thermal energy storage. Changes induced by thermal cycling on the main physical and mechanical properties of basalt have been presented. Basalt has been identified as a suitable storage material for concentrated solar tower power plants (up to 700 °C).